Additive manufacturing and non-destructive testing of topology-optimised aluminium components. Issue 3 (2nd July 2020) - Senck, Sascha; Happl, Michael; Reiter, Michael; Scheerer, Michael; Kendel, Manuel; Glinz, Jonathan; Kastner, Johann
ABSTRACT: Additive manufacturing (AM) unlocks novel industrial possibilities in relation to design optimisation for lightweight structures, e.g. in aerospace applications. However, the inherent geometric complexity of topology-optimised AM components represents a major challenge for conventional non-destructive testing (NDT) methods. Due to its flexibility and high throughput, industrial X-ray micro-computed tomography (XCT) is the most promising NDT method for AM. In this contribution, we investigate topology-optimised engine brackets that were manufactured from AlSi10 Mg using selective laser melting (SLM). We investigate the respective parts and in-process test coupons in a multiscale approach to be able to extract pore size distributions at different spatial resolutions between 105 and 1.25 µm isometric voxel size. At the lowest spatial resolutions, existing pores cannot be segmented. In contrast, decreasing voxel sizes leads to an increase in total porosity up to 1.53%. Defects like pores in load-carrying areas can profoundly influence the component´s mechanical performance; hence, extensive NDT investigations are mandatory to predict the effect of defects in aluminium AM components.